Pelatihan Pencegahan Kekerasan Seksual pada Anak bagi Pengajar Pusat Pengembangan Anak Kabupaten Rote - Juliana Marlin Y Benu; Rizky Pradita Manafe; Dian Lestari Anakaka (Devotion : Jurnal Pengabdian Psikologi, 2024)
Data on sexual violence againts children in NTT Province continues to increase yearly. Most cases of sexual violence against children occur at home and are commited by those closest to the child, often leaving the child feeling powerless to report the abuse. As a result, the sexual violence can persist for a long time. The challenges in uncovering the sexual violence experienced by children make it essential for adults around them to proactively engage in preventing such cases and to equip themselves with the skills to assist children who experience sexual violence. This community service aims to (1) increase knowledge regarding sexual violence for teachers at child development centers on Rote Island and (2) Provide skills in assisting children who are victims of sexual violence to teachers at child development centers on Rote Island. This community service activity was attended by 15 child development center teachers, 3 men and 12 women. The analysis showed an average increase in pre-test and post-test scores of 17.6 points. The mentoring skills of the participants also improved. This service activity produced several outcomes, such as leaflets on the issue of sexual violence, journal articles, online media publications, and videos of community service activities.